Middle East authoritarianisms : governance, contestation, and regime resilience in Syria and Iran - Heydemann, Steven; Leenders, Reinoud (Stanford studies in Middle Eastern and Islamic societies and cultures., 2013)
The developments of early 2011 have left the political landscape of the Middle East changed but recognizable. Even as urgent struggles continue, it remains clear that authoritarianism will survive this transformational moment. The study of authoritarian governance, therefore, remains essential for our understanding of the political dynamics and inner workings of regimes across the region. The contributors to this volume consider the Syrian and Iranian regimes-what they share in common and what distinguishes them. Too frequently, authoritarianism has been assumed to be a generic des.